Difficult Inhibation (DI) in Patients of Cardiac Surgery of Punjab Institute of Cardiology, Lahore (Medical Forum Monthly, 2021)
Objective: The objective of this study was to determine the frequency of difficult intubation among patients of cardiac surgery in the Punjab Institute of cardiology.Study Design: Observational StudyPlace and Duration of Study: This study was conducted at the Department of Anesthesia, Punjab Institute of Cardiology from October 2020 to February, 2021.Materials and Methods: All the patients of age 20 to 80 years of either gender undergoing elective or emergency cardiac surgery meeting the American Society of Anesthesiologists’ (ASA) grades I-IV undergoing general anesthesia with endotracheal intubation were included in the study. Patients were not told anything about this classification and no medication was given beforehand to any of them. While in the Operation Theater, patients ECG was monitored along with all other vitals. Any patient in which Cormack Lehane grade III and IV if seen on laryngoscopic view or if bougie was used in patients with Cormack grade II, was defined as a case of DI.Results: Data of the physical examination was collected and late analyzed to calculate the BMI of these patients. Among all the 110 patients enrolled, the mean value of BMI was 31.2 + 5.9. 50 of 110 patients had a BMI of more than 30, falling into obesity. While categorizing the patients into ASA grading, 71 patients were of grade III or IV and rest 39 patients were of ASA grade I or II. The frequency of difficulty intubation DI among these patients of our study was 23.6% (26 patients among the total 110 patients). Among these patients who had DI, female gender was dominantly affected but the difference of DI among male and female gender was not statistically significant, (p = 0.77).Conclusion: Around one fourth of the patients undergoing cardiac surgery can have difficult intubation, depending upon the age, gender, BMI, ASA grading and some other factors. Pre-operative assessment of the patients by the anesthetist should be done thoroughly taking in account the risk factors and Cormack Lehane grade of the patient. If pre-op assessment is not done properly, patients can have DI and end up into cricothyrotomy and lead to significant increase in morbidity and mortality. Studies should be done in all fields of surgery to see the incidence of DI, correlating it with various risk factors.